Hubungan Skor Albumin-Bilirubin (ALBI) Pra Hepatektomi dengan Kesintasan Pasca Hepatektomi pada Pasien Karsinoma Hepatoseluler - Desbagiska, Ewasa; Nuryanto, Khairul; Murti, Sinta (ITKES Wiyata Husada Samarinda, 2023)
Hepatocellular carcinoma (HCC) is a type of primary liver cancer developed from hepatocytes. HCC can be aggressive and has a poor prognosis. Patients’ prognosis can depend on tumor characteristics and liver functions. Albumin-Bilirubin (ALBI) is an objective indicator for assessing liver function. This study focuses on investigating the correlation between ALBI grade for pra-hepatectomy and post-hepatectomy survival among patients with hepatocellular carcinoma. It was an analytical observational study applying cohort study retrospective approach. The data were taken from patients’ medical records at Abdoel Wahab Sjahranie Regional Public Hospital using total sampling method. The research samples were patients with hepatocellular carcinoma undergoing hepatectomy therapy and fulfilling inclusion and exclusion criteria. The statistical analysis used Kaplan Meier test. The findings revealed that out of 22 samples, eight patients were classified as ALBI grade for pra-hepatectomy class 1. 14 patients were classified as class 2. The survival rate shown based on ALBI grade class 1 was 87.5% and class 2 was 62.4%. Log Rank test indicated a significant correlation with p value <0.001. It can be concluded that ALBI grade for pra-hepatectomy and posthepatectomy survival are significantly correlated among patients with hepatocellular carcinoma. Keywords : ALBI Score, Hepatocellular Carcinoma, Survival Rate.